2001
DOI: 10.1097/00042307-200107000-00016
|View full text |Cite
|
Sign up to set email alerts
|

The use of synthetics in the treatment of pelvic organ prolapse

Abstract: Despite an improved understanding of pelvic anatomy and organ function and advances in surgical techniques, long-term success rates in pelvic surgery are still variable (3-59%), but can reach up to 92% in the case of associated procedures. The major causes of recurrent pelvic prolapse after corrective surgery are related to patient factors, such as poor tissues, impaired healing processes and chronic pathological increases in intra-abdominal pressure. Other causes of failure are, however, probably related to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
18

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 47 publications
2
59
0
18
Order By: Relevance
“…Tal reação pode ser desejada ou inconveniente, quando causa efeitos compressivos ou obstrutivos. Portanto, tal fenômeno deve sempre ser lembrado e a tela implantada sem tensão 13 . A utilização de tela monofilamentar e macroporosa (tipo I) é a mais apropriada, porém na literatura são descritas taxas de extrusão dessa tela entre 6 e 25% 15 .…”
Section: Descritoresunclassified
See 1 more Smart Citation
“…Tal reação pode ser desejada ou inconveniente, quando causa efeitos compressivos ou obstrutivos. Portanto, tal fenômeno deve sempre ser lembrado e a tela implantada sem tensão 13 . A utilização de tela monofilamentar e macroporosa (tipo I) é a mais apropriada, porém na literatura são descritas taxas de extrusão dessa tela entre 6 e 25% 15 .…”
Section: Descritoresunclassified
“…Vários procedimentos cirúrgicos foram propostos para a correção do prolapso genital; no entretanto, apesar do crescente desenvolvimento das técnicas cirúrgicas e do conhecimento da anatomia pélvica, os resultados não são completamente satisfatórios. As taxas de recidivas do prolapso de órgãos pélvicos após correção cirúrgica variam de 22% a 92% 13,14 . O uso de telas na cirurgia reconstrutora pélvica se baseia na premissa de que as distopias são consequentes ao enfraquecimento dos tecidos naturais.…”
unclassified
“…Similarly, other authors have observed tears or breaks in the endopelvic fascia of women with pelvic floor prolapse during reconstructive surgery [9] . Regardless of the etiology of the laxity, many reconstructive surgeons have argued that prolapsed vaginal tissue is weak and, alone, cannot provide support for adequate repair, creating a need for further tissue reinforcement [10] . The current available options for graft materials applicable to pelvic floor support include autologous fascia, cadaveric fascia, porcine dermis, porcine small intestine submucosa, and synthetic mesh [11] .…”
Section: Discussionmentioning
confidence: 99%
“…За цих умов пологи і травми розглядаються як про-вокуючі фактори [6,8,29]. І що яскравіші прояви дисплазії на поліорганному рівні, то частішими є швидкі та стрімкі пологи, і так само частіше виникає пролапс геніталій, який більш виражено маніфестує, важче піддається хірургічній корекції та зумовлює високу частоту рецидивів [5].…”
Section: вдосконалення ведення післяопераційного періоду у жінок із пunclassified